Simultaneous Evaluation of Lung Anatomy and Ventilation Using 4D Respiratory‐Motion‐Resolved Ultrashort Echo Time Sparse MRI. Issue 2 (25th September 2018) - Feng, Li; Delacoste, Jean; Smith, David; Weissbrot, Joseph; Flagg, Eric; Moore, William H; Girvin, Francis; Raad, Roy; Bhattacharji, Priya; Stoffel, David; Piccini, Davide; Stuber, Matthias; et al.
Abstract : Background: Computed tomography (CT) and spirometry are the current standard methods for assessing lung anatomy and pulmonary ventilation, respectively. However, CT provides limited ventilation information and spirometry only provides global measures of lung ventilation. Thus, a method that can enable simultaneous examination of lung anatomy and ventilation is of clinical interest. Purpose: To develop and test a 4D respiratory‐resolved sparse lung MRI (XD‐UTE: eXtra‐Dimensional Ultrashort TE imaging) approach for simultaneous evaluation of lung anatomy and pulmonary ventilation. Study Type: Prospective. Population: In all, 23 subjects (11 volunteers and 12 patients, mean age = 63.6 ± 8.4). Field Strength/Sequence: 3T MR; a prototype 3D golden‐angle radial UTE sequence, a Cartesian breath‐hold volumetric‐interpolated examination (BH‐VIBE) sequence. Assessment: All subjects were scanned using the 3D golden‐angle radial UTE sequence during normal breathing. Ten subjects underwent an additional scan during alternating normal and deep breathing. Respiratory‐motion‐resolved sparse reconstruction was performed for all the acquired data to generate dynamic normal‐breathing or deep‐breathing image series. For comparison, BH‐VIBE was performed in 12 subjects. Lung images were visually scored by three experienced chest radiologists and were analyzed by two observers who segmented the left and right lung to derive ventilation parameters in comparison with spirometry. Statistical Tests: Nonparametric paired two‐tailed Wilcoxon signed‐rank test; intraclass correlation coefficient, Pearson correlation coefficient. Results: XD‐UTE achieved significantly improved image quality compared both with Cartesian BH‐VIBE and radial reconstruction without motion compensation ( P  < 0.05). The global ventilation parameters (a sum of the left and right lung measures) were in good correlation with spirometry in the same subjects (correlation coefficient = 0.724). There were excellent correlations between the results obtained by two observers (intraclass correlation coefficient ranged from 0.8855–0.9995). Data Conclusion: Simultaneous evaluation of lung anatomy and ventilation using XD‐UTE is demonstrated, which have shown good potential for improved diagnosis and management of patients with heterogeneous lung diseases. Level of Evidence: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;49:411–422.